Active Drug-Using Women Use Female-Initiated Barrier Methods to Reduce HIV/STI Risk: Results from a Randomized Trial. (23rd September 2013) - Gollub, Erica; Cyrus-Cameron, Elena; Armstrong, Kay; Boney, Tamara; Mercer, Delinda; Fiore, Danielle; Chhatre, Sumedha
Abstract : Background . We tested an original, woman-focused intervention, based on body empowerment, and female-initiated barrier methods, including the female condom (FC) and cervical barriers. Methods . Eligible women were >= 18 years of age, HIV seronegative, and active drug users, reporting 30% or greater unprotected sex acts. Both controls (C) and intervention (I) participants received enhanced HIV/STI harm reduction counseling. I participants underwent 5 additional weekly group sessions. We compared change in frequency of unprotected vaginal intercourse across arms at 12 months. Results . Among 198 enrolled women, over 95% completed followup. Two-thirds were African-American; most of them used crack, had a primary partner, and reported sex exchange. In paired t -tests from baseline to followup, the frequency of unprotected vaginal sex dropped significantly for I (primaryP < 0.00, nonprimaryP < 0.002 ) and C (primaryP < 0.008, nonprimaryP < 0.000 ) arms with all partners. The difference in change across arms was of borderline significance for primary partner (P = 0.075 ); no difference was seen for nonprimary partner (P = 0.8 ). Use of male condom and FC increased with both partner types over time, but more consistently among I women. Conclusion: The "value-added" impact of the intervention was observed mainly with primary partners. Body knowledge with routine FC counseling should be incorporated into interventions for drug-using women.